Measuring air quality using Arduino via APC220 radio data module: article - Haris, Muhamad Harnika Rifhan (2014)
The purpose of this paper is to present and design a device that could monitor air quality in a certain place even in indoor or outdoor for human healthcare. This device could detect a Particulate Matter 2.5 (PM2.5) for an air quality in the area. This paper presents the system development by using Matlab for graphical indicator, and using Arduino UNO as an input/output data to detect dust and gas quality. Using the Arduino device, it uses Optical Sharp Dust Sensor to measure air quality for existence of a dust. Also using an analog gas sensor (QM-NG1) for detecting hydrogen that could give out an alarm for a gas leak. And its uses LM35 to measure a temperature at a measured place. For this prototype, this paper proposes using APC220 as a connection between prototype and serial main monitor on a computer by using RF wireless radio connection. All the value has been mentioned will be interpreted in MATLAB. This research project is useful for air quality for department of environment. Air quality monitoring, PM2.5 detection, Arduino UNO.